2020
DOI: 10.1080/00275514.2020.1759978
|View full text |Cite
|
Sign up to set email alerts
|

Nivicolous Trichiales from the austral Andes: unexpected diversity including two new species

Abstract: Nivicolous myxomycetes are a group of amoebozoan protists dependent on long-lasting snow cover worldwide. Recent fine-scale analysis of species diversity from the austral Andes revealed high intraspecific variability of most taxa, suggesting independent evolutionary processes and significant differences in species compositions between the Northern (NH) and Southern (SH) Hemispheres. The present study is the second part of this analysis based on representatives of Trichiales. A total of 173 South American colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 59 publications
1
11
1
2
Order By: Relevance
“…Subclade H2. Subclade H2 encompassed the three Perichaena species studied that form plasmodiocarps, as previously reported by Ronikier et al (2020). However, a broader representation of P. vermicularis revealed that this taxon encompasses cryptic diversity, comprising distinct non-sister species, as detected with Calomyxa metallica (clade D).…”
Section: Clade Hsupporting
confidence: 60%
See 4 more Smart Citations
“…Subclade H2. Subclade H2 encompassed the three Perichaena species studied that form plasmodiocarps, as previously reported by Ronikier et al (2020). However, a broader representation of P. vermicularis revealed that this taxon encompasses cryptic diversity, comprising distinct non-sister species, as detected with Calomyxa metallica (clade D).…”
Section: Clade Hsupporting
confidence: 60%
“…Within the three orphan taxa, Trichia varia presents pilate spores and capillitium ornamented with smooth spirals (García-Cunchillos et al, 2021b), similar to subclade H3 species. Hemitrichia crassifila (baculate spores, capillitium with spirals bearing cylindrical projections) highly resembles Hemitrichia intorta, while we did not recover such phylogenetic affinities, as pointed out in Ronikier et al (2020). Remarkably, the species Cornuvia serpula shows distinctive, large discs embracing the capillitium filaments (sometimes named rings) and unique cristate reticulate-like spores (Estrada-Torres et al 2015).…”
Section: Clade Hcontrasting
confidence: 45%
See 3 more Smart Citations